Effect of mineral admixtures on the correlation between ultrasonic velocity and compressive strength for self-compacting concrete - Ulucan, Zuelfue C.; Turk, Kazim; Karatas, Mehmet (Maik Nauka/Interperiodica/Springer, 2008)
Nondestructive testing of concrete is preferred due to its distinct advantage over conventional compression tests. The evaluation by nondestructive methods of the actual compressive strength of concrete in existing structures is based on empirical relations between strength and nondestructive parameters. The aim of the study was to investigate the effects of different types and dosages of mineral admixtures on the correlation between ultrasonic pulse velocity (UPV) and compressive strength for self-compacting concrete (SCC). Different proportions of fly ash (FA) and silica fume (SF) are used as the mineral admixtures in replacement of portland cement (PC) in SCC. The work focused on concrete mixes having a slump flow between 700 and 710 mm. Specimens were prepared and cured in standard 20 +/- 3 degrees C water for periods of 3, 7, 28, and 130 days. At the end of each curing period, compressive strength and UPV were determined. Tests were carried out on 150-mm cubic specimens to evaluate the compressive strength and UPV of SCC. The results of this research indicate that reductions in the compressive strength due to SF were lower than those for FA at all levels of replacement at 3 days, while both UPV and compressive strength at early ages were very low at all levels of mineral admixtures. However, with the increase of the curing period, both UPV and compressive strength of SCCs containing both FA and SF increased. The correlation between UPV and compressive strength is also exponential for SCCs containing both FA and SF. However, constants for each pozzolana were different for each level of replacement of PC in SCCs.
Keywords: Cement Mortar; Pulse; Aggregate